Health-related quality of life, lifestyle habits and chronic pain in individuals with knee pain – a 2-year follow-up study. - Sylwander, Charlotte; Haglund, Emma; Larsson, Ingrid; Andersson, Maria L. E. (Scandinavian Journal of Primary Health Care, 2025)
Introduction: Knee pain increases the risk of developing chronic widespread pain (CWP) and knee osteoarthritis (KOA). The prevalence of CWP and KOA has increased, and there is a need for early prevention. Therefore, the aim was to examine the associations of health-related quality of life (HRQoL) and lifestyle habits with chronic pain at a two-year follow-up in individuals with knee pain. Methods: A two-year longitudinal cohort study including 251 individuals aged 30–60 years reporting knee pain at baseline. HRQoL was measured via the Short-Form General Health Survey (SF-36), and lifestyle habits included questions on overweight, physical activity, diet, alcohol and tobacco use. Pain was assessed with a pain mannequin. Differences in health status and lifestyle habits over time in groups with unchanged no chronic pain (NCP), transitioned to less and more pain, and unchanged CWP were analysed using Wilcoxon's, McNemar's and Friedman's tests. Multinominal regression analysis was performed to study associations with reporting chronic pain at follow-up. Results: Reporting better HRQoL across various SF-36 concepts and normal weight at baseline was associated with reporting NCP after two years. A few changes were made regarding HRQoL and lifestyle habits over the course of two years, but an increase in general health was associated with transitioning to less pain. Conclusions: During primary care visits for knee pain with a combination of overweight or lower HRQoL, individuals should receive comprehensive attention to prevent the development of CWP. Future studies should investigate the associations further.